Exposure to secondhand smoke in health institutions and sources of knowledge: a cross-sectional study from the city of Bulawayo, Zimbabwe - Ndlovu, Nkanyiso (Pan Afr Med J, 2020)
INTRODUCTION: annually, many people die due to being exposed to secondhand smoke (SHS) which they experience at a number of premises that include health institutions. Scientists agree that there is no safe exposure level to SHS, however, in the City of Bulawayo many people are exposed to SHS. There are great expectations from communities for health professionals to reduce SHS exposure-related morbidity and mortality. This study sought to establish exposure to SHS in health institutions and sources of knowledge on SHS. METHODS: a cross-sectional study, with participants randomly selected from residents visiting the 13 municipal revenue halls in the City of Bulawayo, was conducted. Data were collected through a structured questionnaire and were analyzed by performing descriptive and multivariate logistic regression. RESULTS: 26.3% (N = 419) of respondents who had been to health institutions in the previous 30 days had been exposed to SHS within those institutions. Almost all the respondents (85.4%) had never received a lesson on SHS from a health professional or had last received one three months before the survey. Furthermore, 74% of respondents had not seen posters on SHS or had last seen one more than three months before the survey. CONCLUSION: health professional should collaborate with other professionals in the fight against exposure to SHS as evidenced by the high prevalence of exposure in the health institutions and low health education given on SHS exposure in the City of Bulawayo